Spesialisasi Penyidik Polri Polda Papua dalam Pemberantasan Tindak Pidana Korupsi - Asdar Djabbar (Kyadiren, 2019)
The purpose of this study was to determine the urgency of Polri's specialization in eradicating Corruption Crimes. The research method used was an empirical juridical research method which was carried out to seek and obtain data directly in the field according to the problems studied. This research was carried out at the Papua Regional Police and the Papua Police Sub-Directorate of Corruption by conducting interviews with the Karo HR and the Head of the Papuan Police's Head of Corruption Crime Sub-Directorate. The results showed that the role of the National Police investigators, especially the Papuan Police in enforcing the law on corruption, was due to several causes, including: juridical, psychological, technical, skills, and facilities and infrastructure factors.